HUBUNGAN MOTIVASI DAN PERILAKU PEMBELAJARAN DENGAN METODE DARING TERHADAP PERSEPSI PEMBELAJARAN KEMAMPUAN BERBICARA BAHASA INGGRIS DI ERA COVID 19 PADA MAHASISWA TINGKAT 3B DAN 3D STIKES YATSI TANGERANG - Purwani, Retno; Sari, Destiyana Kurnia; Winarni, Lastri Mei (Nusantara Hasana Berdikari, 2021)
Students will successfully achieve their learning outcomes if they have a desire to learn. This desire is called motivation. A student's speech ability can be seen if the assessment techniques used are appropriate, because assessment is important in the learning process, especially speaking learning to know and understand students in the development of their skills or speaking skills. Objective: knowing the relationship between motivation and learning behavior with online methods to the perception of learning English proficiency in the covid-19 era in students level 3b and 3d Stikes Yatsi year 2020. Method: The method that researchers use is descriptive research of correlation. The selection of samples using the total sampling method is all Students level 3b and 3d at STIKes YATSI which amounted to 115 people. Data analysis is done using chi-square. Results: p-value in the relationship of motivation to the perception of learning English proficiency by 0.099 > 0.05 which means no relationship. While in learning behavior with online methods of learning perception of English speaking skills obtained p-value of 0.282 > 0.05 which means there is no relationship.Conclusion: students who have high learning motivation have the will to obtain good grades so as to achieve these goals students learn well and diligently.